Myocardial injury after pulmonary vein isolation: fire versus ice. (14th October 2021) - Morgado Gomes, A R; Antonio, N S C; Silva, S; Madeira, M; Sousa, P; Elvas, L; Goncalves, L
Abstract: Introduction: The cornerstone of atrial fibrillation (AF) catheter ablation is pulmonary vein isolation (PVI), either using point-by-point radiofrequency ablation (RF) or single-shot ablation devices, such as cryoballoon ablation (CB). However, achieving permanent transmural lesions is difficult and pulmonary vein (PV) reconnection is common. Elevation of high-sensitivity Troponin I (hsTnI) may be used as a surrogate marker for transmural lesions. Still, data regarding the comparison of hsTnI increase after PVI with RF or cryo-energy is controversial. Purpose: The aim of this study is to compare the magnitude of hsTnI elevation after PVI with CB versus RF using ablation index guidance. Methods: Prospective study of 60 patients admitted for first ablation procedure of paroxysmal or persistent AF in a single tertiary Cardiology Department. Thirty patients were submitted to PVI using CB and 30 patients were submitted to RF, using CARTO® mapping system and ablation index guidance. Patients with atrial flutter were excluded. Baseline characteristics were compared between groups, as well as hsTnI before and after the procedure. Results: Mean age was 57.9±12.3 years old, 62% of patients were male and 77% had paroxysmal AF. There were no significant differences between groups regarding gender, age, prevalence of hypertension, dyslipidaemia, diabetes, obesity or AF type. There was also no significant difference in electrical cardioversion need during the procedure. HsTnI median value before ablation was 1.90±1.98 ng/dL. Postprocedural hsTnI was significantly higher in CB-group (6562.7±4756.2 ng/dL versus 1564.3±830.7 ng/dL in RF-group; P=0.001). Regarding periprocedural complications, there was only one case of mild pericardial effusion in RF-group associated with postablation hsTnI of 1180.0 ng/dL. Conclusions: High-sensitivity Troponin I was significantly elevated after PVI, irrespective of the ablation technique. In CB-group, hsTnI elevation was significantly higher than in RF-group. This disparity may reflect more extensive lesions with cryoablation, without compromising safety. Longterm studies are needed to understand whether this hsTnI elevation is predictive of a lower AF recurrence rate. Funding Acknowledgement: Type of funding sources: None.